Elderly Knowledge About Lancia Posyandu in Sinar Sabungan Village, Bonatua Lunasi District, Tobasa Regency - Ismi Noer Fadilah; Chika Ade Hendranti (PT Inovasi Pratama Internasional, 2023)
Elderly Posyandu is an integrated service post for the elderly in a certain area that has been agreed upon, which is driven by the community where they can get health services. This study aims to determine the knowledge of the elderly about the elderly Posyandu in the Village of Sinar Sabungan, District of Bonatua Lunasi, Tobasa Regency. This research method is descriptive, where the elderly population is 57 people, the sampling technique is done by total sampling, and the sample that meets the research criteria and fills out a questionnaire is 57 respondents. Data collection was carried out from 21 April 2021 to 24 May 2021 using a questionnaire which consisted of two parts: the first was about demographic data, the second part was Knowledge of the elderly about the Elderly Posyandu in Sinar Sabungan Village, Bonatua Lunasi District, Tobasa Regency. From the data analysis it is known that out of 57 respondents there are 51 respondents (89.5%) who have good knowledge, 6 respondents (10.5%) who have sufficient knowledge and no respondent (0%) who has less knowledge. This shows that the knowledge of the elderly about the elderly posyandu is good. It is recommended that health center staff continue to improve the elderly posyandu program and provide health education as well as socialize the existence and benefits of elderly posyandu services.